First descriptions of two new amber species of Cyphomyrmex from Mexico and the Dominican Republic (Hymenoptera: Formididae). - Andrade, Maria L. (Contributions to Entomology = Beiträge zur Entomologie, 2003)
Two new amber species of Cyphomyrmex represented by a single specimen each are described. C. maya n. sp. is based on a single worker from Mexican amber. C. taino n. sp. is described on an alate gyne from Dominican amber. C. maya and taino are members of the rimosus group of Kempf (1964) and of the foxi subgroup of Snelling & Longino (1992). Among the two known Jamaican representatives of the foxi subgroup, C. maya resembles foxi. The worker of maya shares with the one of foxi developed mesosomal spines. C. maya can be easily differentiated from foxi mainly by the propodeum profile with two spiniform teeth instead of a longitudinal carina forming two succeeding obtuse teeth, by the shorter scapes, by the postpetiole with smaller and less pointed dorsal projections and by the smaller size. The gyne of taino resembles the gyne of foxi in general shape, but taino differs from foxi by its smaller size, by the shorter scapes and by the postpetiole with lower, much smaller and rounded dorsal projections. The gyne of taino also resembles the worker of maya in head shape, but taino can be easily distinguished from maya by the denser pilosity and sculpture. Nomenclatural Acts maya de Andrade, 2003 (Cyphomyrmex), spec. n. taino de Andrade, 2003 (Cyphomyrmex), spec. n.